Land Cover Change on Flood Potential in Ulakan Watershed Padang Pariaman Regency - Irmayanti, Silvia; Syarief, Azhari (JURNAL BUANA, 2025)
This study aims to identify changes in land cover in the Batang Ulakan Watershed of Padang Pariaman Regency and determine the potential for flooding in the Batang Ulakan Watershed of Padang Pariaman Regency. This type of research uses quantitative descriptive method with classification analysis of flood potential value using weighted and scoring method. Basic physical data related to land cover change is a data series in 2013 and 2022 which is overlaid to determine changes in land cover in the Ulakan watershed area. Potential flood parameters analyzed are slope, soil type, rainfall, and land cover. The results of the analysis showed that the Ulakan watershed area experienced land cover changes within 10 years from 2013 to 2022 amounting to 13.415,78 ha or 62% of the total area. By using the overlay method based on 4 parameters of flood potential (slope, soil type, rainfall, and land cover), three classifications of flood potential levels were obtained, namely a very potential level of 10.784,3 ha or 50%, and a potential level of 9,423,2 ha or 44%, and a non-potential level of 1,273.9 ha or 6% of the total area of the Ulakan watershed area of Padang Pariaman Regency.